The Differences Result Of Platelets Count In K3edta Blood At Room Temperature (24-29°C) And Refrigerator (2-8°C) For 2 Hours - Ratih Hardisari (Jurnal Teknologi Kesehatan (Journal of Health Technology), 2018)
Examination of platelets count is one of hematological examinations. This examination used K3EDTA blood samples which is better to be examined directly. The large number of blood samples in hospital causes nurses who take the sample do not directly bring them to laboratory and process of changing shifts on laboratory workers allows for a delay, causing platelets count decrease, so the K3EDTA blood sample should be stored at the refigerator (2-8°C) when examination delays. This study was aimed to find out the differences result of platelets count in the K3EDTA blood stored at room temperature (24-29ºC) and refigerator (2-8oC) for 2 hours. This study is a quantitative approach to the design of observational analytic with cross-sectional study, where K3EDTA blood tests stored at room temperature (24-29ºC) and refigerator (2-8º C) at the same time. The subjects of this research were 30 blood samples were taken using vein puncture from Health Analyst students aged around 18-21 years old and had no history of blood disorders, especially abnormalities of platelet count. The result of platelets count examination of K3EDTA blood stored in refigerator (2-8°C) for 2 hours tend to be higher than in K3EDTA blood samples stored at room temperature (24-29°C), with p value 0.046 (p <0,05). The average number of platelets in the K3EDTA blood stored at room temperature (24-29°C) was 276,000 cells/mm3 and stored in refrigerator (2-8°C) was 304 000 cells/mm3. The conclusion is there are significant differences in the result of platelets count in the K3EDTA blood stored at room temperature (24-29ºC) and refigerator (2-8°C) for 2 hours.